A Case of Mycoplasma Pneumoniae-Associated Encephalomyelitis in a 16-Year-Old Female Presenting to an Adult Teaching Hospital. Issue 6 (January 2013) - Tran, Hieu; Allworth, Anthony; Bennett, Cameron
We report a rare cause of encephalitis that is not often described in the adult clinical setting. Our case was a 16-year-old female who presented with a clinical picture of viral encephalitis; however, magnetic resonance imaging showed a demyelinating lesion of the left frontal lobe. In this age group, differential diagnoses of acute demyelination encephalomyelitis and multiple sclerosis were entertained. Further investigations demonstrated positive Mycoplasma pneumoniae serology. As a result, a diagnosis of Mycoplasma pneumoniae -associated encephalitis was made based on a process of exclusion.